Odontogenic Keratocyst in Anterior Mandible: A Case Report - mohammadi, maryam; shahabinejad, mehdi; mohtasham, nooshin; mohajer tehran, farnaz (Journal of Case Reports in Dental Medicine, 2022)
Odontogenic Keratocyst (OKC) is a non-inflammatory developmental odontogenic cyst arises from cell rest of the dental lamina and most commonly occurs in the posterior of the mandible. This study describes the occurrence of this lesion in a rare location in a 36 years old female patient.